Dampak adanya Desa Wisata Edelwais Wonokriti terhadap Perekonomian Masyarakat Tengger - Meuthia Ratu Citra; Atikah Nurun Nisail Jamilah; Liya Irdzina (Pinus Publishing, 2025)
Edelweis Tourism Village is one of the tourism that can have a major impact on the economy of the surrounding community. The presence of this tourism village not only introduces the beauty of nature and local culture, but also opens up opportunities for the community to improve their standard of living through the creative industry and tourism sector. The purpose of this study is to analyze the contribution of the Edelweiss tourism village to the local economy. It focuses on increasing aspects of community income, job creation, micro, and strengthening small and medium enterprises (SMEs). The results of the study indicate that the presence of the Edelweiss tourism village increases tourist visits and promotes economic sectors such as hospitality, cooking, crafts and transportation. Local residents are increasingly involved in economic activities as service providers and business owners, leading to increased family income. In addition, the tourism village plays a role in maintaining local culture and introducing natural possibilities to the outside world. Overall, the Edelweiss tourism village can have a positive impact on the community's economy and become a sustainable model of tourism development.